2012
DOI: 10.1093/jat/bks066
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Synthetic Cannabinoids in U.S. Athletes: Initial Findings

Abstract: A number of synthetic cannabinoids such as JWH-018 and JWH-073 have been incorporated into "spice" products. Despite having labels warning against human consumption, the products are smoked for their cannabinoid-like effects and the extent of their use by athletes has not been adequately described. Urine samples collected from 5,956 athletes were analyzed by high-performance liquid chromatography-tandem mass spectrometry for the presence of JWH-018, JWH-073, and their metabolites. Metabolites of JWH-018 and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 5 publications
3
18
1
Order By: Relevance
“…Thus, it is not surprising that our observed percentage of patients with a history of SC use was higher than that in the general population. Several previous studies have reported that the prevalence of cannabis and SC use is higher among psychotic patients than among non-psychotic patients [45,47,48,53,54], and these results were supported by the results of this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, it is not surprising that our observed percentage of patients with a history of SC use was higher than that in the general population. Several previous studies have reported that the prevalence of cannabis and SC use is higher among psychotic patients than among non-psychotic patients [45,47,48,53,54], and these results were supported by the results of this study.…”
Section: Discussionsupporting
confidence: 90%
“…Instead, we compared the observed prevalence rates of SC use with the estimated prevalence rates of SC use in previous studies. The studies in question estimated that the prevalence of SC use was 1% in the general population, 2-10% among students and 10% among groups with high rates of drug use (e.g., nightclubbers) [45,47,48,53,54]. Compared with these estimated rates, the prevalence of SC use in the present sample seems very high.…”
Section: Discussioncontrasting
confidence: 50%
“…In this age group, ever SC use was first reported to be around 10% (e.g., Barratt et al, 2013;Forrester, Kleinschmidt, Schwarz, & Young, 2012;Gunderson, Haughey, AitDaoud, Joshi, & Hart, 2014;Hu, Primack, Barnett, & Cook, 2011;Vandrey et al, 2012), but the recently published results of a self-reported study, including almost 15,000 participants from different countries, revealed lifetime use to be more prevalent: 16.8% (Winstock & Barratt, 2013). Accumulating evidence demonstrates the increasing popularity of SCs amongst soldiers (Bebarta, Ramirez, & Varney, 2012;Loeffler, Hurst, Penn, & Yung, 2012) and athletes (Heltsley et al, 2012;M€ oller et al, 2011).…”
Section: Users Routes Of Administration Dosagesmentioning
confidence: 99%
“…Extraction of SCs using SPE has been used in blood and serum [91], urine [92][93][94][95][96] and oral fluid [45,97,98]. Different types of SPE columns can be used depending on the cost, availability and the nature of the analytes of interest.…”
Section: Solid Phase Extractionmentioning
confidence: 99%